Heritage as learning. Why should community learning and education focus on cultural heritage? - Kurantowicz, Ewa (Adult Education Discourses, 2024)
The article relies on theory and research to argue that the concept of cultural heritage should be incorporated into adult education and learning studies. The focus on this issue has been prompted by a paradigmatic change in the way that researchers and practitioners in the cultural heritage field understand and define this phenomenon. Particularly relevant in this context is addressing and highlighting the links between cultural heritage and identity (formation), as well as re-defining the social values and meanings of cultural heritage. In this approach, the central role of adult learning (as a process, a strategy, a mechanism and a trajectory) is indispensable for the new perspective on ‘heritage’ to be recognized and applied. Adult education researchers and practitioners have long been involved in cultural education, promotion of social activism and museum education, but a new opening and radical change in “cultural heritage” sciences enable adult education researchers, among other scholars, to join the interdisciplinary debate on so-called Heritage Studies. The argument also draws on the partial research findings of the EU_CUL project partners, which showcase the interconnectedness of learning, heritage and community and leave no doubt that the past values and meanings of cultural heritage must be renegotiated for the present and the future.